Framing a Supermantra: Ecotourism, Engagement and Conceptualisations of 'Good' Development. Issue 3 (1st September 2016) - Singleton, Benedict E.
Abstract : Ecotourism as a development strategy is often attractive – rather than exhausting natural resources, local communities can benefit from their conservation. Ecotourism-based conservation thus becomes conceived as a 'win-win' for local communities and narrative-based campaigns have emerged to promote it. This article investigates how a narrative of ecotourism and development is created and what social and political implications this has. Drawing on media studies and political ecology literature, this article looks at a global campaign, the Manta Ray of Hope (MRH), which utilises such a narrative to engender enthusiasm for the conservation of mobulids (manta and mobula rays) and to lobby for their protection. Multimodal analysis is employed to interrogate the MRH media materials, examining how threats to mobulids are framed. Through this framing a discourse is created, the discourse of the supermanta, which contains a win-win narrative asserting that mobulid fishing can be converted into ecotourism to the benefit of both fishers and mobulids. The supermanta is a supermantra: it presents a homogenised picture of diverse species and situations obscuring differences between the contexts and communities where mobulids are fished. This also hides the fact that any changes to resource usage will have winners and losers. This analysis shows that the supermanta reiterates the message of other, criticised, conservation campaigns. The article concludes by suggesting that conservation campaigns like the MRH utilise a more open, inclusive approach to framing, allowing a wider range of voices to contribute to the supermanta.